Plankton Communities - Pereira, Leonel; Marta Gonçalves, Ana (IntechOpen, 2022)
Plankton is a group of small organisms that are passively displaced by water, that is, they are dragged by marine tides and currents. Marine plankton, which includes organisms such as protozoa, microalgae, small crustaceans, and jellyfish, play an important role in maintaining the health and balance of the ocean and its complex food chains. Over three sections and eight chapters, this book provides a comprehensive overview of zooplankton and phytoplankton as well as their environmental and economic importance.